Actinomyces Produces Defensin-Like Bacteriocins (Actifensins) with a Highly Degenerate Structure and Broad Antimicrobial Activity - Sugrue, Ivan (J Bacteriol, 2020)
We identified a strain of Actinomyces ruminicola which produces a potent bacteriocin with activity against a broad range of Gram-positive bacteria, many of which are pathogenic to animals and humans. The bacteriocin was purified and found to have a mass of 4,091 ± 1 Da with a sequence of GFGCNLITSNPYQCSNHCKSVGYRGGYCKLRTVCTCY containing three disulfide bridges. Surprisingly, near relatives of actifensin were found to be a series of related eukaryotic defensins displaying greater than 50% identity to the bacteriocin. A pangenomic screen further revealed that production of actifensin-related bacteriocins is a common trait within the genus, with 47 being encoded in 161 genomes. Furthermore, these bacteriocins displayed a remarkable level of diversity with a mean amino acid identity of only 52% between strains/species. This level of redundancy suggests that this new class of bacteriocins may provide a very broad structural basis on which to deliver and design new broad-spectrum antimicrobials for treatment of animal and human infections. IMPORTANCE Bacteriocins (ribosomally produced antimicrobial peptides) are potential alternatives to current antimicrobials given the global challenge of antimicrobial resistance. We identified a novel bacteriocin from Actinomyces ruminicola with no previously characterized antimicrobial activity. Using publicly available genomic data, we found a highly conserved yet divergent family of previously unidentified homologous peptide sequences within the genus Actinomyces with striking similarity to eukaryotic defensins. These actifensins may provide a potent line of antimicrobial defense/offense, and the machinery to produce them could be used for the design of new antimicrobials given the degeneracy that exists naturally in their structure.